Gross Anatomical Study on Gut Associated Lymphoid Tissue of Pig (Sus scrofa) - Urmila, T. Sai (Indian Journal of Veterinary Anatomy, 2019)
The gross anatomical study was conducted on gut associated lymphoid tissue of 18 pigs. The small and medium type of Peyer’s patches were oval to rectangular in duodenum and oval and elliptical in jejunum and proximal ileum. The terminal ileum showed a large elongated Peyer’s patch, which extended continuously into ileocaecal junction. Due to the close association of the follicles, the Peyer’s patches appeared as a continuous longitudinal band in terminal part of ileum. The ileocaecal junction also contained a few button shaped patches. In large intestine, the solitary lymphnodules were distributed randomly throughout the length of middle and distal colon and rectum whereas, these were absent in caecum and proximal colon.